2009
DOI: 10.3168/jds.2008-1452
|View full text |Cite
|
Sign up to set email alerts
|

Use of β-cyclodextrin to decrease the level of cholesterol in milk fat

Abstract: This study was carried out to determine optimum conditions (beta-cyclodextrin concentration, mixing time, and holding time) for cholesterol removal from pasteurized nonhomogenized milk at 4 degrees C on a commercial scale by adding beta-cyclodextrin in a specially designed bulk mixer tank. The beta-cyclodextrin (0.4, 0.6, 0.8, and 1.0%) removed from 65.42 to 95.31% of cholesterol at 4 degrees C in 20 min. Treatment of milk with 0.8 and 1.0% (wt/vol) beta-cyclodextrin was no better than treatment with 0.6% beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 19 publications
7
43
0
Order By: Relevance
“…Yen and Tsai (1995) treated lard with b-CD to remove cholesterol; no changes in fatty acid composition of the lard occur after the b-CD treatment. Similar results were obtained by Alonso et al (2009) who found no significant difference between the fatty acid composition of untreated milk and milk treated with 0.6% b-CD.…”
Section: Effects Of B-cd On Fatty Acid Composition Of Treated Camel Hsupporting
confidence: 77%
See 1 more Smart Citation
“…Yen and Tsai (1995) treated lard with b-CD to remove cholesterol; no changes in fatty acid composition of the lard occur after the b-CD treatment. Similar results were obtained by Alonso et al (2009) who found no significant difference between the fatty acid composition of untreated milk and milk treated with 0.6% b-CD.…”
Section: Effects Of B-cd On Fatty Acid Composition Of Treated Camel Hsupporting
confidence: 77%
“…About 90-95% of cholesterol from lard was removed with 10% b-CD within 30 min of mixing. However, cholesterol removal was slightly decreased when samples were stirred for 2 h. This finding may be due to the stability of complexes between b-CD and cholesterol during longer mixing times (Lee et al 1999;Alonso et al 2009). Makoto et al (1992) reported that 91.1 and 94.…”
Section: Effect Of Stirring Time and B-cd Concentration On Reduction mentioning
confidence: 76%
“…Beta-cyclodextrins (beta-CDs) have been used to effectively remove cholesterol from animal products, improving their nutritional characteristics (Han et al, 2008). Among the studied foods are milk (Alonso, Cuesta, Fontecha, Juarez, & Gilliland, 2009;Kim, Ahn, & Kwak, 2004;Kwak et al, 2004), butter (Kim, Jung, Ahn, & Kwak, 2006), cream (Han, Kim, Ahn, & Kwak, 2007;Shim, Ahn, & Kwak, 2003), mayonnaise (Jung, Ha, Ahn, & Kwak, 2008), cheese (Bae, Kim, & Kwak, 2008;Han et al, 2008;Kim, Han, Ahn, & Kwak, 2005), egg yolks (Chiu, Chung, Giridhar, & Wu, 2004;Rojas et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The most efficient method to reduce cholesterol was directly adding β-CD to egg-derived yolk, which produced a dramatic decrease of 90 % in the egg-derived yolk cholesterol content. The effectiveness of this method was shown in other studies performed with different matrices (Alonso et al 2009;Jung et al 2005). However, despite this unquestionable effectiveness, the drawback of this process is clear; β-CD inevitably remains in the product, and it is not an approved ingredient in some countries, and the cost is rather high (Lv et al 2002).…”
Section: Resultsmentioning
confidence: 65%
“…β-Cyclodextrins is a cyclic oligosaccharide consisting of seven glucopyranose units with a central cavity similar in diameter to a cholesterol molecule and with affinity for non-polar components, which allows for a highly specific interaction with cholesterol (Astray et al 2009;Del Valle 2004). This interaction readily occurs at temperatures ≤4°C, making it ideal for refrigerated products (Alonso et al 2009). β-Cyclodextrins can be added directly to egg yolk to chelate cholesterol and can then be removed by centrifugation, or β-CD can be immobilized to minimize contamination of food, enabling its reuse after treatment to release the bound cholesterol.…”
Section: Introductionmentioning
confidence: 98%